Karakteristik Alkitabiah Kepemimpinan Hamba dan Implikasinya Bagi Gereja di Era Digital - Marunduri, Elman; Rahayu, Esti Rahayu; Rambing, Royke J. (Jurnal Ilmiah Wahana Pendidikan, 2025)
Church leaders nowadays lack an understanding of Biblical servant leadership because many of them come from lay backgrounds without theological knowledge. That is why church leaders in the digital era need to understand and possess the Biblical characteristics of servant leadership. The research method used in this study is library research, applying the four steps of data analysis from Miles and Huberman. The findings reveal that Biblical servant leadership is leadership that serves or prioritizes the interests of others. There are nine Biblical characteristics of servant leadership and six most prominent implications in this study, all of which will encourage the church and its leaders to play a greater role for their followers and the wider community